The Impact of Sales Growth, Information Asymmetry, Financial Distress and CEO Retirement on Prudence Accounting in the Transportation Sub-Sector Listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 Period - Khisanah, Afifah; Riswan, Riswan (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The purpose of this study is to determine the impact of sales growth, information asymmetry, financial distress and CEO retirement on the implementation of prudence accounting in transportation sub-sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The type of research is quantitative research with secondary data. The sample selection in this study used a purposive sampling technique with a final number of 45 data on transportation sub-sector companies listed on the Indonesia Stock Exchange for 3 years. The results of this study indicate that sales growth, information asymmetry, financial distress and CEO retirement partially have a negative and significant effect on prudence accounting. Simultaneous testing found that sales growth, information asymmetry, financial distress and CEO retirement have a significant effect on prudence accounting.